Durability Studies on the Recycled Aggregate Concrete in China over the Past Decade: A Review. (28th July 2019) - Ma, Zhiming; Tang, Qin; Yang, Dingyi; Ba, Guangzhong
Abstract : Since China hosted the Olympic Games in 2008, a mass of construction and demolition (C&D) wastes were produced with the rapid urbanization construction. Recycling the C&D waste into recycled aggregates (RA) is an effective method for reducing the amount of C&D wastes. Many studies on the properties of RA and the durability of recycled aggregate concrete (RAC) were conducted in China over the past decade. Due to the restrictions of various languages, some valuable studies on the durability of RAC are hard to be acquired by the scholars around the world. Therefore, this paper is developed to review the studies on the durability of RAC in China, and the shrinkage behavior, chloride permeability, carbonation behavior, and freeze-thaw resistance of RAC are, respectively, introduced. Considering the waste concrete, bricks, and ceramics used in preparing RA are frequently mixed together in China, this study proposes an index of average water absorption rate to quantify the effects of RA types, quality, and replacement percentages on the durability of RAC. Meanwhile, the relationship between the average water absorption rate of RA and the durability parameters of RAC is established. Finally, the improving methods of RAC durability are introduced, and the RA particle shaping and carbonation modification are emphasized.